Analysis of Renin-Angiotensin-Aldosterone System Gene Polymorphisms in Essential Hypertension in Javanese Indonesian. (June 2015) - Irijanto, Fredie; Harsoyo, Sapto; Nurochmah, Oom; Zulaela,; Sja'bani, Mochammad; Tomino, Yasuhiko
Abstract : Background: The renin-angiotensin-aldosterone system (RAAS) plays an important role in the regulating of blood pressure. The genetic polymorphisms of RAAS genes have been extensively studied among ethnic groups in the relation with essential hypertension with conflicting results. Objective: This is the first study population in Indonesia which aims to determine the association of angiotensinogen (AGT M235T), angiotensin II type 1 receptor A1166C and angiotensin-converting enzyme I/D gene polymorphisms with essential hypertension. Method: The study was conducted in Mlati District, Yogyakarta Province from 2008 to 2012. From 71, 348 population, 7, 695 subjects were selected by age-adjusting and exclution criteria. After stratified random sampling, subjects were devided into hypertension and normotension groups. The AGT M235T and AGT1R A1166C polymorphisms were identified with PCR-RFLP and ACE I/D was with PCR assays. Clinical data for two groups were compared by the Student t-test and frequency of genotype and the allele were with x 2 . Result: The RAAS genetic susceptibility to the essential hypertension were analyzed by odds ratio (OR) analysis. The study indicated that the individuals carry allele 235T (MT + TT) and A1166C (AA + AC) had a significant risk of developing essential hypertension (p < 0.05). However, ACE I/D genotypes were analyzed collectively, those genotypes were not associated with essential hypertension. Conclusions: These results showed that the angiotensinogen M235T and angiotensin II type 1 receptor A1166C may contribute to the increasing risk of essential hypertension.